VD_FINDINFO Décision / 2013 / 1044 vom 18. Dezember 2013 - VD Tribunal cantonal (2013)
DÉTENTION PRÉVENTIVE, RISQUE DE RÉCIDIVE, PROLONGATION | 221 al. 1 let. c CPP (CH), 222 CPP (CH), 227 CPP (CH), 393 al. 1 let. c CPP (CH)